Transcriptome sequencing and developmental regulation of gene expression in Anopheles aquasalis. - André L Costa-da-Silva; Osvaldo Marinotti; José M C Ribeiro; Maria C P Silva; Adriana R Lopes; Michele S Barros; Anderson Sá-Nunes; Bianca B Kojin; Eneas Carvalho; Lincoln Suesdek; Mário Alberto C Silva-Neto; Anthony A James; et al. (PLoS Neglected Tropical Diseases, 2014)
BACKGROUND:Anopheles aquasalis is a major malaria vector in coastal areas of South and Central America where it breeds preferentially in brackish water. This species is very susceptible to Plasmodium vivax and it has been already incriminated as responsible vector in malaria outbreaks. There has been no high-throughput investigation into the sequencing of An. aquasalis genes, transcripts and proteins despite its epidemiological relevance. Here we describe the sequencing, assembly and annotation of the An. aquasalis transcriptome. METHODOLOGY/PRINCIPAL FINDINGS:A total of 419 thousand cDNA sequence reads, encompassing 164 million nucleotides, were assembled in 7544 contigs of ≥ 2 sequences, and 1999 singletons. The majority of the An. aquasalis transcripts encode proteins with their closest counterparts in another neotropical malaria vector, An. darlingi. Several analyses in different protein databases were used to annotate and predict the putative functions of the deduced An. aquasalis proteins. Larval and adult-specific transcripts were represented by 121 and 424 contig sequences, respectively. Fifty-one transcripts were only detected in blood-fed females. The data also reveal a list of transcripts up- or down-regulated in adult females after a blood meal. Transcripts associated with immunity, signaling networks and blood feeding and digestion are discussed. CONCLUSIONS/SIGNIFICANCE:This study represents the first large-scale effort to sequence the transcriptome of An. aquasalis. It provides valuable information that will facilitate studies on the biology of this species and may lead to novel strategies to reduce malaria transmission on the South American continent. The An. aquasalis transcriptome is accessible at http://exon.niaid.nih.gov/transcriptome/An_aquasalis/Anaquexcel.xlsx.